2020
DOI: 10.1111/jcmm.15195
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin suppresses tumour growth and metastasis through degradation of PAK1 in oesophageal squamous cell carcinoma

Abstract: Oesophageal squamous cell carcinoma (ESCC), the most common form of oesophageal malignancies in the Asia-Pacific region, remains a major clinical challenge. In this study, we found that ivermectin, an effective antiparasitic drug that has been approved for patients to orally treat onchocerciasis for over 30 years, displayed potent antitumour activity against ESCC cells in vitro and in nude mice. We demonstrated that ivermectin significantly inhibited cell viability and colony formation, and induced apoptosis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Studies have also demonstrated that ivermectin induces cytostatic autophagy in breast cancer, and inhibits proliferation of ovarian cancer and oesophageal squamous cell carcinoma, by inhibition of PAK1 protein [ 98 100 ]. Moreover, it induces apoptosis in various other cancer such as melanoma by inhibition of ROS-TFE3 dependent autophagy; in leukemia by increasing chloride ions influx and ROS production; and in colon cancer cells via blocking the WNT/TCF pathway [ 101 103 ].…”
Section: Mechanism Of Action Of Anti-parasitic Drugsmentioning
confidence: 99%
“…Studies have also demonstrated that ivermectin induces cytostatic autophagy in breast cancer, and inhibits proliferation of ovarian cancer and oesophageal squamous cell carcinoma, by inhibition of PAK1 protein [ 98 100 ]. Moreover, it induces apoptosis in various other cancer such as melanoma by inhibition of ROS-TFE3 dependent autophagy; in leukemia by increasing chloride ions influx and ROS production; and in colon cancer cells via blocking the WNT/TCF pathway [ 101 103 ].…”
Section: Mechanism Of Action Of Anti-parasitic Drugsmentioning
confidence: 99%
“…Ivermectin was reported to have an anti-proliferative effect on esophageal squamous cell carcinoma (ESCC) cells. Ivermectin also significantly inhibits ESCC cell growth, migration and invasion by blocking PAK1 signaling (Chen et al 2020). We showed that ivermectin decreased A549 cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Juarez et al [75] and Antoszczak et al [76] have reviewed the anticancer effects of ivermectin at high concentrations (0.1-100 μM or doses of 3-40 mg/kg) in tissue culture and in mice. The modes of action of ivermectin on different types of cancer are proposed to involve different mechanisms: (i) the multidrug-resistance transporter protein [77]; (ii) Akt/mTOR [78] and WNT-TCF pathways [79]; (iii) purinergic receptors [80]; (iv) PAK-1 [81]; (v) the cancer-related epigenetic deregulators SIN3A and SIN3B, RNA helicase; (vi) effects on mammalian tubulin polymerization and depolymerization dynamics [82]; and (vii) preferential targeting of cancer stem-cell-like populations [83]. The potential for repurposing ivermectin for cancer treatment remains to be established, as does the mechanisms of action.…”
Section: Anticancer Effects Of Ivermectinmentioning
confidence: 99%